Episodic sediment supply to alluvial fans: implications for fan incision and morphometry - A. S. Leenman; A. S. Leenman; B. C. Eaton (Earth Surface Dynamics, 2022)
Sediment supply is widely believed to be a key control on alluvial fan morphology and channel dynamics. Although the sediment supply to natural fans is rather episodic, experimental studies of alluvial fans often use constant sediment supply rates, making it difficult to relate fan dynamics to the magnitude and frequency of sediment supply in the field. This paper presents a series of experiments designed to test the impact of episodic sediment supply on fan evolution and dynamics. We compare four experiments, each with the same mean sediment supply but different durations of high- and low-supply periods. The experiments show that fan morphology and channel dynamics respond systematically to the temporal elongation of sediment supply oscillations: longer supply cycles generate flatter fans with more trenched channels. These results highlight how different basin conditions might generate different fan morphologies: supply-limited basins with intermittent sediment supply might generate fans that are flatter than expected. Our results raise the question of whether a constant sediment supply in experimental models can adequately characterise the dynamics of natural fans in the field. We therefore suggest that experimental modellers should include variability when investigating fan responses to sediment supply.